2022
DOI: 10.1002/jmv.27647
|View full text |Cite
|
Sign up to set email alerts
|

Association of atrial fibrillation with infectivity and severe complications of COVID‐19: A nationwide cohort study

Abstract: Infection is associated with the occurrence, recurrence, and progression of atrial fibrillation (AF), and is also closely related to poor prognosis. However, studies of the relationship between infectivity and severe complications of coronavirus infectious disease-19 (COVID-19) with a history of AF are limited.To estimate infectivity and severity of complications in COVID-19 patients with a history of AF, this study was done. From the Korean nationwide COVID-19 dataset, 212 678 participants with at least one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The fact that atrial fibrillation appears as a predictor for the development of HF is consistent with findings found in other studies in which patients with atrial fibrillation had higher rates of mortality and complications [24]. In another study, it was observed that 5% of patients hospitalized for COVID-19 developed a first episode of atrial fibrillation and had higher rates of hypertension and HF than those who did not develop atrial fibrillation [25].…”
Section: Discussionsupporting
confidence: 88%
“…The fact that atrial fibrillation appears as a predictor for the development of HF is consistent with findings found in other studies in which patients with atrial fibrillation had higher rates of mortality and complications [24]. In another study, it was observed that 5% of patients hospitalized for COVID-19 developed a first episode of atrial fibrillation and had higher rates of hypertension and HF than those who did not develop atrial fibrillation [25].…”
Section: Discussionsupporting
confidence: 88%
“…Coronavirus disease 2019 (COVID-19) is spreading rapidly [ 1 , 2 , 3 , 4 , 5 ]. Herd immunity is important for the prevention and suppression of the spread of COVID-19, and vaccination is an essential requirement for herd immunity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), which causes coronavirus disease 2019 (COVID‐19), is still spreading around the world. Although the severity decreased after the omicron variation became the main type, people with comorbidities still require respiratory care or may even die 1‐4 . Accordingly, achieving herd immunity is important to limit COVID‐19 cases as much as possible, and vaccination is one available strategy to attain herd immunity 5 .…”
Section: Introductionmentioning
confidence: 99%